Strategic use of Iranian bread wheat landrace accessions for genetic improvement: Core set formulation and validation. (20th December 2020) - Vikram, Prashant; Franco, Jorge; Burgueño, Juan; Li, Huihui; Sehgal, Deepmala; Saint‐Pierre, Carolina; Ortiz, Cynthia; Singh, Vaibhav Kumar; Sneller, Clay; Sharma, Achla; Tattaris, Maria; Guzman, Carlos; et al.
Abstract: Iranian wheat landrace accessions (IWAs) were collected from country‐wide farm fields and market places in 1935 by a professor at the University of Tehran and shared with University of California at Davis, California. IWAs were further submitted to the genebank of International Maize and Wheat Improvement Center (CIMMYT), Mexico. 2, 403 IWAs from CIMMYT's genebank were assayed by DArT‐seq technology to assess genetic diversity. No apparent ecogeographic patterns related to genetic diversity were detected, probably due to long‐term transport and frequent interchange of landraces among farmers. A multivariate clustering procedure combining genotypic and phenotypic information was used in selecting a core‐set, which represented 15% of the hexaploid wheat accessions included in this study. This subset captured an estimated 93% of rare (frequency <0.05) alleles. Multisite phenotypic data (India, Mexico) validated the ability of the core‐set in detecting useful variants. Potential donor accessions for multiple traits (disease resistance, zinc concentration) were identified from the core‐set for wheat‐breeding. This report illustrates a breeder friendly robust core‐set formulation strategy for harnessing the useful genetic variation stored in the genebanks.